Prospecção fitoquímica e atividade biológica de plantas medicinais da família asteraceae do bioma pampa - Stüke, Caroline Ziegler (2012)
The species selected for this study were: Pluchea sagittalis, Baccharis pentodonta and Baccharidastrum triplinervium, all belonging to the Asteraceae family. The extracts and fractions from leaves and roots of three species of medicinal plants in Rio Grande do Sul were obtained by different extraction processes (cold, the hot water extraction and soxhlet) and subjected to HPLC analysis. These extracts and fractions were subjected to different fractionations were isolated where some secondary metabolites (chlorogenic acid derivatives and flavonoids). In the leaves of Pluchea sagittalis were isolated the secundary metabolites 3,4- dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid and 4,5-dicaffeoylquinic acid. The crude extract of the root of the same species were isolated the same three metabolites 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid and 4,5-dicaffeoylquinic acid and the 1,3, 5-tricaffeoylquinic acid. Baccharis pentodonta were isolated metabolites 5,7,4'- trihydroxy-6-methoxy-luteolin and 5,7,3,4 - tretrahydroxy-6-methoxy-flavon for leaves and their metabolites 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid, 4,5- dicaffeoylquinic acid and 3-feruloyl-5-caffeoylquinic acid. The root Baccharidastrum triplinervium were isolated metabolites 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid and 4,5-dicaffeoylquinic acid already isolated from other species previously worked. The structures of these metabolites isolated was characterized by NMR analysis and high resolution mass. Additionally extracts and fractions obtained were tested in vitro and to determine their antimicrobial, antioxidant and enzyme inhibition against the enzyme DPP IV and POP. Most of the extracts and fractions tested showed antimicrobial activity by the method of microdilution around 0,5 mg ml-1 and moderate antioxidant activity by the method of free radical (DPPH) and the ethyl acetate fraction showed the highest potential. Among the activities of enzyme inhibition, the activity was more pronounced compared to POP, with only the crude extracts of the roots of B. pentodonta and B. triplinervium presented themselves as potential inhibitors of the enzyme DPP IV.